Dominant transposition-deficient mutants of maize Activator (Ac) transposase. - Kunze, R (1993)
The maize transposable element Activator (Ac) encodes a transposase (TPase) protein, whose DNA-binding domain is located in a basic region around aa 200. The N-terminal 102 aa of the TPase are not required for the transposition reaction. In transfected petunia protoplasts, we analyzed the protein levels of the N-terminally truncated TPase and mutants thereof and the corresponding transposition frequencies. The TPase protein forms large insoluble aggregates at high expression levels. There is no proportionality observed between TPase levels and transposition frequency. Twenty-one mutations (of 26), which are distributed over the whole length of the protein, inactivate the TPase completely. By coexpressing inactive mutant and active truncated TPase, it was found that several mutations have a trans-dominant inhibitory effect. Among those are two DNA-binding-deficient mutants, indicating that inhibition of the active TPase is not caused by competition for the binding sites on the transposon. Accordingly, Ac TPase acts as an oligo- or multimer formed by protein-protein interactions. Peculiarly, two mutants lacking 53 and 98 aa from the C terminus that are themselves transpositionally inactive lead to an increased excision frequency when they are coexpressed with the active truncated TPase.